Frestas da vida sobre trilhos eléctricos: modos e modelos de subjetivação no metrô de São Paulo - Frei, Altieres Edemar (2013)
This research which has as its final stop the present essay-dissertation had as its point of departure an investigation concerning the means and the ways of subjectivity crossed, involved, forged and reinforced by the daily movements displayed by the citizens in São Paulo´s underground (considered the most crowded underground system in the world in its peak hours). We understand that in the current stage of sophistication in the control society, in a time defined by some as late capitalism or economic globalization, the politics concerned with accommodating, conditioning and piling up the citizens-users of the underground transportation system demand more emphasis and aesthetical elegance than the semiotic strategies have provided up to now. In our research, we state that biopower politics are being applied in the underground transportation system, and those politics seem to be of high relevance not only to its own operations, as well as to the urban configuration. In this sense, we consider the underground transportation system as a state-device. The underground is a fold of São Paulo metropolis in state of metastasis. Our investigative method was anchored by the theoretical references able to provide lights and follow our hypothesis, and also by the ethnographic incursions done in order to gather samples of the life gapsdisplayed over the electric tracks: stereotypes, boredom, lines of escape, dialogues biopolitical samples, in a wider sense. As results of this investigation, we also present single propositions of intervention on the daily life of underground users, with the suggestion of occupying its sonic territory through a project of audio compositions specially produced to be accessed during the underground trips